Building Student Character and Ethics in Elementary Schools with Prophetic Values through Islamic Teachings - Hulkin, M.; Zakaria, Abd Razak (Educative: Jurnal Ilmiah Pendidikan, 2024)
Character education based on prophetic values in Islamic teachings is relevant and essential. Prophetic values such as honesty, responsibility, compassion, and justice in Islam have great potential to form excellent and ethical student characters. This study attempts to build the character and ethics of students in elementary schools by integrating prophetic values in education based on Islamic teachings. This research used a descriptive qualitative approach conducted at Pematang Mesuji State Elementary School. The study was conducted online through the WhatsApp application using an interview instrument based on existing facts. Data were obtained through in-depth interviews with teachers and principals at Pematang Mesuji State Elementary School, South Sumatra. The results showed that integrating prophetic values effectively strengthens students' character and prepares them to face moral challenges in daily life. The implications of this study highlight the importance of school leadership support and diversification of teaching methods to achieve more holistic character education goals at the primary level.